Implementation of Education Report Cards in the Preparation of School Account Documents - Siregar, Surianti (Pusdikra-Publishing.com, 2024)
The purpose of this study is to discuss the Implementation of the Education Report Card in the Preparation of School Account Documents, the conclusion of this paper is that the Education Report Card is one of the programs of the Merdeka Belajar curriculum issued by the Ministry of Education and Culture in the 9th episode which is said to be an improvement on the Education Quality Report Card. Of the many types and sources of data needed in the implementation of this activity, it is certainly possible that there will be obstacles in the final assessment process in the Education Report Card which then disrupts the implementation of the preparation of the RKAS which is very dependent on the results of the Education Report Card. Therefore, before actually implementing and maximizing the use of the Education Report Card, it is necessary for the government to maximize the previous education data collection program or system that has been running so as not to interfere with the implementation of the next program. The government must focus more on providing professional resources for each educational institution that plays a role in data management, to providing adequate facilities for the implementation of each data collection program.